2017
DOI: 10.1108/ijem-01-2016-0011
|View full text |Cite
|
Sign up to set email alerts
|

Impact of psychological capital on occupational burnout and performance of faculty members

Abstract: Purpose The purpose of this paper is to examine the impact and interrelation between positive psychological capital and occupational burnout among faculty associates of technical and professional training institutions. Design/methodology/approach In total, 282 faculty members from 17 technical institutions were selected from the province of Punjab, Pakistan. Results were drawn using bivariate correlation and linear regression on the data that were collected through adopted questionnaire. Findings Results o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
53
1
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(63 citation statements)
references
References 53 publications
4
53
1
5
Order By: Relevance
“…Salam (2017) also found that teachers who have psychological capital can more easily develop job satisfaction due to their positive thoughts and mental resources embedded in psychological capital might make them more resistant to the development of intent to leave. As Pu et al (2017) and Rehman et al (2017) found, psychological capital strengthens teachers against the negative effects of various experiences at work. Teachers who have lower levels of psychological capital may be more vulnerable to negative effects of various experiences at work that can damage their job satisfaction and organizational commitment levels.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Salam (2017) also found that teachers who have psychological capital can more easily develop job satisfaction due to their positive thoughts and mental resources embedded in psychological capital might make them more resistant to the development of intent to leave. As Pu et al (2017) and Rehman et al (2017) found, psychological capital strengthens teachers against the negative effects of various experiences at work. Teachers who have lower levels of psychological capital may be more vulnerable to negative effects of various experiences at work that can damage their job satisfaction and organizational commitment levels.…”
Section: Discussionmentioning
confidence: 95%
“…There are many studies consistently showing that psychological capital is positively related to in-role and extra-role performance and positive attitudes (job satisfaction, organizational commitment, and psychological well-being), while it is negatively related to misbehaviors and negative attitudes (intent to leave, cynicism, work stress, and anxiety) (Avey et al, 2011;Luthans & Youssef-Morgan, 2017). More specifically, related research showed a negative relationship between psychological capital and negative attitudes such as stress (Bradley, 2014), anxiety (Liu et al, 2013), intent to leave (Tüzün, Çetin & Basım 2014), and burnout (Pu, Hou, Ma, & Sang, 2017;Rehman, Qingren, Latif, & Iqbal, 2017;Wang, Chang, Fu, & Wang, 2012); and a positive relationship between psychological capital and positive attitudes such as job satisfaction (Akçay, 2012;Erkuş & Fındıklı, 2013;Çetin & Basım, 2011;Kaplan & Biçkes, 2013;Luthans & Youssef, 2004;Schulz et al, 2014), job involvement (Yüksel & Akdağ, 2011), organizational commitment (Dirzyte, Patapas, Smalskys, & Udaviciute, 2013), and motivation (Mortazavi, Yazdi, & Amini, 2012).…”
mentioning
confidence: 99%
“…Second, the results showed that there is a significant negative correlation between the overall psychological capital and involuntary absenteeism. In addition, Rehman' s study on teachers' job burnout showed that teachers' positive psychological capital has a significant impact on eliminating job burnout and improving job performance (Rehman et al, 2017).…”
Section: The Influence Of Psychological Capital On Job Burnout and Jomentioning
confidence: 99%
“…This would allow the identification of groups of teachers who are vulnerable to a greater or lesser degree. Based on the work reviewed, which, from a variable-centered focus, has examined the relationship between psychological capital and burnout in teachers [31,[36][37][38][39], we hypothesize that the profile with low levels of psychological capital (in the four components) will have higher scores for burnout, and in contrast, the profile with high psychological capital (high scores in the four components) will have the lowest indexes of burnout.…”
Section: Introductionmentioning
confidence: 99%